EFFECTIVENESS OF A COMBINED MINIMALLY INVASIVE STRATEGY FOR EARLY CHILDHOOD CARIES PREVENTION: A PROSPECTIVE CONTROLLED CLINICAL STUDY (American Journal of Research in Humanities and Social Sciences, 2026)
Early childhood caries (ECC) remains one of the most prevalent chronic diseases in pediatric populations worldwide and continues to pose a significant clinical and public health challenge. Although individual minimally invasive interventions have demonstrated effectiveness in controlling early carious lesions, limited evidence exists regarding the clinical impact of integrated, risk-based minimally invasive models that simultaneously address caries activity, lesion progression, and patient-related behavioral outcomes.